Concrete Durability Performance Against Seawater As Curing And Mixing Water - Zulfira Mirani; mukhlis, Mukhlis; Oni Guspari; Andini Meysi Ullanda; Yosi Arista (Universitas Negeri Padang, 2024)
This research aims to determine the effect of seawater on concrete durability and to assess the compressive strength of concrete based on variations in concrete mixtures and curing methods. The tests conducted include testing the characteristics of coarse and fine aggregate materials to obtain accurate concrete mix planning, followed by compressive strength testing after curing for 3, 7, 14, 21, and 28 days with four different mix and curing variations. The results show that in variation 1, the compressive strength of concrete cured with seawater for 14 days was 9.81% higher than that cured with freshwater. In variation 2, the compressive strength of concrete mixed with seawater and freshwater cured for 3 days was 43.91% higher compared to seawater curing. In variation 3, the compressive strength of concrete with a freshwater-seawater mix cured for 14 days was 44.65% higher than that of the seawater-only mix. In variation 4, the compressive strength of concrete with a seawater-freshwater mix cured for 3 days was 15.54% higher than that of the freshwater-only mix.